pH-Controlled fluorescence switching in water-dispersed polymer brushes grafted to modified boron nitride nanotubes for cellular imaging - Kalay, Saban; Stetsyshyn, Yurij; Donchak, Volodymyr; Harhay, Khrystyna; Lishchynskyi, Ostap; Ohar, Halyna; Panchenko, Yuriy; Voronov, Stanislav; Çulha, Mustafa (Beilstein Journal of Nanotechnology, 2019)
pH-Switchable, fluorescent, hybrid, water-dispersible nanomaterials based on boron nitride nanotubes (BNNTs) and grafted copolymer brushes (poly(acrylic acid-co-fluorescein acrylate) – P(AA-co-FA)) were successfully fabricated in a two-step process. The functionalization of BNNTs was confirmed by spectroscopic, gravimetric and imaging techniques. In contrast to “pure” BNNTs, P(AA-co-FA)-functionalized BNNTs demonstrate intense green fluorescence emission at 520 nm. Under neutral or alkaline pH values, P(AA-co-FA)-functionalized BNNTs are highly emissive in contrast to acidic pH conditions where the fluorescent intensity is absent or low. No increase in the absorption was observed when the suspension pH was increased from 7 to 10. The functionalized BNNTs are easily taken up by human normal prostate epithelium (PNT1A) and human prostate cancer cell lines (DU145) and are suitable for further evaluation in cellular imaging applications.
Keywords: boron nitride nanotubes; cellular imaging; fluorescence; pH switching; polymer brushes; surface modification